Naskah Angling Darma Ambya Madura - A. Syukur Ghazali (Universiti Kebangsaan Malaysia, 2001)
This paper examines the Madurese version of Angling Darma, a Javanese story about the life of a king who leaves his kingdom as dharma to expiate his sins. It is written in Madurese dialect of Sumenep and is assumed to have been rewritten in a different form with adaptation and adoption of many words and expressions from the Javanese language. The existence of this version refutes Drewes’s claim that only the Javanese version without any Islamic features, is found in Madura. An examination of the text reveals that Islamic features are apparent either directly (such as reference to the Prophet) or indirectly. This text consists of eight parts of written tembang. Types and numbers of tembang for each ‘canto’ (division of poems) vary from one to the other, depending on the variation and length of events narrated